2011
DOI: 10.4103/1995-705x.86016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term pranayama and meditation on cardiovascular functions in healthy individuals

Abstract: Context:Asana, pranayama, and meditation are three main techniques of yoga practiced in India over thousands of years to attain functional harmony between the body and mind. Recent studies on long-term yogic practices have shown improvements in cardiovascular functions.Aim:The present study was conducted to ascertain if a short-term practice of pranayama and meditation had improvements in cardiovascular functions in healthy individuals with respect to age, gender, and body mass index (BMI).Settings and Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 3 publications
3
60
0
3
Order By: Relevance
“…3,6 It has been reported that regular Yoga practice resulted in decrease in resting respiratory rate. 7 It has also been reported that short term Yoga practice resulted in significant improvement in BHT 8,9 and MVV. 10 In a study with subjects between the ages of 40 to 60 years with no previous Yoga experience, 80 % showed improvement in breath holding time after the completion of an intensive Yoga program.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 It has been reported that regular Yoga practice resulted in decrease in resting respiratory rate. 7 It has also been reported that short term Yoga practice resulted in significant improvement in BHT 8,9 and MVV. 10 In a study with subjects between the ages of 40 to 60 years with no previous Yoga experience, 80 % showed improvement in breath holding time after the completion of an intensive Yoga program.…”
Section: Introductionmentioning
confidence: 99%
“…Esta modulação autonômica no ioga é mediada pela modificação dos padrões respiratórios que desencadeiam vários mecanismos centrais e autonômicos, bem como ajustes mecânicos e hemodinâmicos causando modificações tônicas e fásicas da função cardiovascular (RAGHURAJ et al, 1998;ANKAD et al, 2011).…”
Section: Resultsunclassified
“…Em uma revisão sistemática da literatura, Ospina et al (2008) O ioga tem mostrado benefícios terapêuticos em pessoas saudáveis (ANKAD et al, 2011) e para diferentes patologias, incluindo a HA, como terapia complementar no seu tratamento (McCAFFREY, 2005).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The physiological effects of Yoga training that have been previously reported include the inhibition of body weight gain, reduction in cholesterol levels and blood pressure along with improvement in immune function as well as beneficial psychological effects. [5][6][7][8][9][10] Obesity, hypertension and dyslipidemia are one of the major risk factor for cardiovascular disease. The characteristic features of Indian dyslipidemia are a high plasma triglyceride concentration, low high-density lipoprotein (HDL) concentration and increased concentration of small dense low-density lipoprotein (LDL) particles.…”
Section: Introductionmentioning
confidence: 99%